ApoB/apoA‐I Ratio and Lp(a) Associations With Aortic Valve Stenosis Incidence: Insights From the EPIC‐Norfolk Prospective Population Study. Issue 16 (20th August 2019) - Zheng, Kang H.; Arsenault, Benoit J.; Kaiser, Yannick; Khaw, Kay‐Tee; Wareham, Nicholas J.; Stroes, Erik S. G.; Boekholdt, S. Matthijs
Abstract : Background: Apolipoprotein B/apolipoprotein A‐I (apoB/apoA‐I) ratio and lipoprotein(a) (Lp[a]) are associated with aortic valve stenosis (AVS) disease progression. Clinical characteristics such as age, sex, and presence of concomitant coronary artery disease may strongly modify these associations; however, these effects have not been well defined in longitudinal studies. We set out to assess these associations between apoB/apoA‐I ratio, Lp(a), and AVS incidence in a large population study. Methods and Results: We analyzed data from 17 745 participants (mean age, 59.2±9.1 years; men, 44.9%) in the EPIC‐Norfolk (European Prospective Investigation Into Cancer in Norfolk Prospective Population Study) population study in whom apoB/apoA‐I and Lp(a) levels were measured. Participants were identified as having incident AVS if they were hospitalized or died with AVS as an underlying cause. After a median follow‐up of 19.8 years (17.9–21.0 years) there were 403 (2.2%) incident cases of AVS. The hazard ratio for AVS risk was 1.30 (95% CI, 1.19–1.41; P <0.001) per SD increase in apoB/apoA‐I. Adjusting for age, sex, and coronary artery disease, there was no significant association between apoB/apoA‐I and AVS incidence (hazard ratio, 1.06; 95% CI, 0.97–1.17 [ P =0.215]). Elevated Lp(a) (>50 mg/dL) remained an independent risk factor for AVS after adjustment for age, sex, low‐density lipoprotein cholesterol, and concomitant coronary artery disease (hazard ratio, 1.70; 95% CI, 1.33–2.19 [ P <0.001]). Conclusions: In this population study, apoB/apoA‐I ratio was associated with risk of AVS incidence, especially in younger and female participants and those without concomitant coronary artery disease. Lp(a) was an independent risk factor for AVS incidence. Interventional trials are needed to investigate whether modulating apoB/apoA‐I or lowering Lp(a) can prevent or slow down AVS.